2020
DOI: 10.3390/bdcc4040036
|View full text |Cite
|
Sign up to set email alerts
|

Ticket Sales Prediction and Dynamic Pricing Strategies in Public Transport

Abstract: In recent years, the demand for collective mobility services registered significant growth. In particular, the long-distance coach market underwent an important change in Europe, since FlixBus adopted a dynamic pricing strategy, providing low-cost transport services and an efficient and fast information system. This paper presents a methodology, called DA4PT (Data Analytics for Public Transport), for discovering the factors that influence travelers in booking and purchasing bus tickets. Starting from a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the research of influencing factors of marketing performance, the academic circles use neural network to judge the action intensity of influencing factors, so as to obtain the weight of each influencing factor [1,2]. In the research of marketing performance, neural network method has many advantages, such as multi-factor analysis, strong adaptability, and accurate calculation results, but it also has some disadvantages, such as prone to local minimum and low calculation efficiency [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In the research of influencing factors of marketing performance, the academic circles use neural network to judge the action intensity of influencing factors, so as to obtain the weight of each influencing factor [1,2]. In the research of marketing performance, neural network method has many advantages, such as multi-factor analysis, strong adaptability, and accurate calculation results, but it also has some disadvantages, such as prone to local minimum and low calculation efficiency [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on train ticket pricing indicated that factors such as the number of days passed from booking to departure, departure or arrival time, etc. significantly influence the desired price of customers [4,5]. So, one of the approaches that can adjust pricing considering customer satisfaction, is to pricing regarding factors that significantly influence pricing from a customer point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks such as Facebook and Twitter have become very popular and are receiving increasing attention from the research community, since every day millions of people produce a huge amount of digital data that can be effectively exploited to extract insights concerning human dynamics and behaviors [4]. For example, social media users moving through a sequence of locations in a city or region can create a huge amount of georeferenced data that includes extensive knowledge of human dynamics and mobility behaviors [5,6]. In addition, an ever-increasing volume of urban-related data, with spatial and temporal attributes, poses several challenges related to city management and services, from weather and air quality to public transport to reduce emissions, traffic congestion, and energy costs [7,8].…”
Section: Introductionmentioning
confidence: 99%